Holding pediatric cardiac surgery together: My Serbian experience of 25 years - Stajević, Mila (Frontiers in Pediatrics, 2022)
The pediatric cardiac surgery department was officially founded in Yugoslavia at the Mother and Child Health Institute in Belgrade in February 1982 and provided with cardiac surgery about 80% of children with congenital heart disease in the country. In 1998, after years of political and economical devastation of the country, and thus, congenital heart surgery, this department split into two; the other being formed in another hospital in the same city. I had been positioned as the Head of the Department at a very young surgical age, after returning to my hospital from my training at the Great Ormond Street Hospital in London. The emphasis of this paper are the daily professional challenges, the impact of foreign surgical teams and individuals on our work, the pitfalls, advantages and possibilities, our current surgical results, our future plans and my personal attitude on this profession. The limitation of this investigation is the „half of the story“, and the personalization of the paper.